Winter buzz and summer siesta in Zagreb - perceptual differences in soundscape of the sequence of urban open spaces - Oberman, Tin; Bojanić, Bojana; Šćitaroci, Obad; Jambrošić, Kristian; Kang, Jian (AESOP, 2017)
What makes a good public space? There are many answers to this question, but no definite ones. This ongoing research focuses on perceptual differences within sequences of urban open spaces in the historical city centres of Zagreb, in Croatia, and Sheffield, in the United Kingdom, in the hope of providing some new insights. A harmonious historical setting is perhaps one of the most recognisable visual factors, while soundscape is one of the most elusive. The former can be protected by law as cultural heritage, but the latter changes according to activities and weather conditions, regular or irregular daily or weekly rhythms, or even seasons. Yet both contribute to personal assessments of comfort in public space and in the end, directly to the quality of city life (Carr et al, 1992). Both the chosen locations were recognised as containing sequences of acoustically specific urban open spaces, with different visual presence of historical elements. Studying their perceptual differences and similarities may lead to a better understanding of the importance that soundscape and the authenticity of a heritage setting have in the management and enhancement of urban open spaces. The paper focuses on the sequence in Zagreb known as the Green Horseshoe. It consists of seven squares and one park of approximately the same sizes and shapes, with similar traffic regulation, but different ambiences in their central parts, due to different types of foliage, pavilions and activities. No square on its own conveys a particular aural experience, but in a sequence, they are worth investigating, as the fact that they are nearly the same shape and size eliminates the influence of these factors during comparison. The visual and acoustic properties differ from one square to the next, like the rooms within a Baroque enfilade from the salon to the boudoir – from the square housing the opera building to the Botanical Gardens. The complex was built in the late nineteenth and early twentieth centuries. Today, it forms a vital part of Zagreb’s city centre, where the historical setting has been well preserved (Knežević, 1996). However, not all the urban open spaces in the sequence are equally important or adequately used in terms of their potential.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017